Pengembangan Bahan Ajar Ilmu Pengetahuan Alam Dan Sosial (IPAS) Berbasis Religi - Arofah, Lailatul; Mislikhah; Suhardi, Andi (Perspektif Ilmu Pendidikan, 2024)
The natural and social sciences subjects which are currently called IPAS are a form of creative new curriculum in the independent curriculum, where this curriculum studies natural and social sciences which are designed into one book. Religion-based learning is learning that is integrated with religious values which aims to help students understand and apply religious aspects in their lives, as well as to deepen their understanding of religious beliefs and values. The research method used in developing natural and social science learning materials based on religion for class 4 is the Research and Development (R&D) method. The Research and Development (R&D) method is a research method used to produce certain products, to test the effectiveness of these products. This research uses the ASSURE development model which consists of Analyze learners, State Objectives, Select Strategies, methods, materials, Utilize Technology and Media, Require Learner Participation, Evaluate and Revise. The results of the module specification research show that the Islamic-based thematic module takes the form of print media. Second, namely validation, effectiveness and attractiveness. Based on design expert validation 79%, material expert validation 75%, learning expert validation 80%, based on field tests students in finding attractiveness obtained 88% results, based on the average pre-test and post-test results, namely 61.45 and 91.79 which can provide an assessment of the effectiveness of the module. Based on the results, the module created by the researcher is effective, valid and interesting.